Coral Reef Degradation Due to ‘Ship Grounding' in Indonesia: Case Study of Ship Aground in Bangka-Belitung Waters by Mother Vessel MV Lyric Poet - Idris Idris; Neviaty P. Zamani; Suharsono Suharsono; Fakhrurrozi Fakhrurrozi (Jurnal Ilmiah Perikanan dan Kelautan, 2020)
HighlightDamage to coral reefs by ship aground is twice the area of a football fieldFound four zones of damage including runoff, dune, blow and dispersalMortality of live coral and other benthic biota ranges from 75-100% in the affected locationThe form of damaged live coral growth is predominantly slow growing.Eight hard coral species were found on the IUCN-Redlist list with a vulnerable status.AbstractShip grounding on coral reefs often results in physical and biological damage, including dislodging and removal of corals from reefs, destruction of coral skeletons, erosion and removal of sediment deposits, and loss of three-dimensional complexity. Indonesia, as an archipelagic country, is very vulnerable to various pressures; for example, the case of ship grounding is a great concern of scientists, managers, divers, and sailors themselves. Most of the damage is very severe. The purpose of the research conducted is to identify the condition of the live coral cover, mapping the type and extent of coral reef damage, affected coral species, their conservation status, and to quantify the extent of the area of coral reef damage. Measuring the extent of damage to coral reef ecosystems using the fishbone method, while the level of damage and its impact was measured using the Underwater Photo Transect (UPT) and belt transect method. The event of the grounding of the MV Lyric Poet on the Bangka Waters, Bangka-Belitung Province, has caused damage to the coral reef ecosystem. There are four damage zones identified, i.e., trajectory, mound, propeller, and dispersion zone. Corals are damaged with a total area of 13.540m2; equivalent to twice that of an international football field. Diversity of hard coral found as many as 49 species included in the CITES-Appendix II. A total of eight protected species are included in the IUCN Red List with extinction-prone status.